Outdoor Leadership Theory and Practice - Martin, Bruce; Breunig, Mary; Wagstaff, Mark; Goldenberg, Marni (Human Kinetics, 2017)
Outdoor Leadership, Second Edition, is the definitive text for developing student leadership in outdoor and adventure settings throughout the world. Crafted by an author team internationally recognized for their research, teaching, and experience in outdoor and adventure leadership, this new edition provides students with the foundational knowledge they need to develop as competent professionals in the field.